Thermal properties enhancement of epoxy resins by incorporating polybenzimidazole nanofibers filled with graphene and carbon nanotubes as reinforcing material. (February 2020) - Datsyuk, V.; Trotsenko, S.; Trakakis, G.; Boden, A.; Vyzas-Asimakopoulos, K.; Parthenios, J.; Galiotis, C.; Reich, S.; Papagelis, K.
Abstract: Enhancement of thermal properties of epoxy resins was achieved by incorporation of polybenzimidazole (PBI) fibermats filled with carbon nanomaterials, prepared by the solution electrospinning technique. Different type of carbon nanostructures (carbon nanotubes, graphite flakes, graphene nanoplatelets and carbon black) were compared as fillers in polybenzimidazole fibers. The carbon-PBI-fibermats showed remarkable thermal transport properties and therefore, they were studied as thermal reinforcement material for epoxy composites. Mechanical and thermal properties of produced composites were evaluated and the effectiveness of different types of carbon fillers examined. Results showed that the produced carbon filled fibermats can be used effectively as a thermal reinforcing material in epoxy resins, offering several advantages. Highlights: Epoxy composites were produced by PBI/CNMs fibermats, which were prepared by the solution electrospinning technique. The fabricated composites exhibit extremely enhanced thermal properties compared to neat epoxy resin. The incorporation of the fibermats into epoxy resin also enhanced the mechanical properties of the polymer. Processing method can be extended towards the production of industrial laminated composites with high thermal conductivity.